Process Simulation and Optimization of Anaerobic Co-Digestion - Inayat, Abrar; Ahmed, Shams Forruque; Djavanroodi, F.; Al-Ali, Fatima; Alsallani, Mira; Mangoosh, Shama (Frontiers in Energy Research, 2021)
Anaerobic digestion (AD) is an established method that has been extensively utilized for waste management, waste treatment, and biogas production. Anaerobic co-digestion (AcoD) is regarded as a practical approach to address substrate characteristics and system optimization issues. The distinction between AcoD and mono-digestion is that AcoD has a higher organic loading and significant substrate composition variation. There are many factors involved in AcoD which affect the biogas plant’s production ability and performance. Using response surface methodology (RSM) to forecast the optimal conditions for maximum biogas output, this article provides an overview of the different operational parameters in the AcoD process, modeling of the AcoD process, and overall process optimization. Standard software used for AcoD process simulation are Aspen Plus, SuperPro Designer, BioWin, CFD, and MATLAB. Review addresses design, development, and optimization frameworks for biogas production systems that take numerous aspects into account. The most significant AcoD optimization parameters include temperature, co-substrate concentration, inoculum ratio (percent), and C/N ratio.